MINERALOGICAL COMPOSITION AND PHYSICO-CHEMICAL CHARACTERISTIC OF FOREST LAND SOIL DEVELOPED FROM ACID SEDIMENTARY ROCKS IN RIAU PROVINCE - SUHARTA, NATA; PRASETYO, BAMBANG HENDRO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
Exploitation forest land for food crops agricultural use often limited by drastically change of soil properties and soil characteristics after two or three years of usage. The loose of organic matter through mineralization processes and erosion is causal factor for decreasing fertility of the soils. To study soil properties and soil characteristics as foundation for agricultural use, the forest land derived from sedimentary rock in Riau Province have been studied. The Research result indicates that parent material has great influence on mineral composition, physical and chemical properties of the soils. Soil from sedimentary rock in the study area were very developed, indicated by domination of kaolinite and very low of mineral reserve. Soils derived from claystone have better chemical properties compare to soil derived from sandstone as shown by exchangeable bases, cation exchange capacity, and potential K, but limited by highly Al exchangeable. The physical properties of the soils indicate that the soil is susceptible for erosion and compaction. For that reasons, the exploitation of forest land for agriculturing or forest plantation use need soil conservation practices, avoid the slopping area (>8%) especially for food plantation, and fertilizer. Changing the forest land to agricultural land not only increase mineralization of organic matter but also interrupt biological cycles that influential on decreasing soil fertility.